A importância do ambiente de não-mercado para a formulação da estratégia das empresas produtoras de biodiesel : um estudo usando Grounded Theory - Goulart, Daniel Franco (2018)
Biodiesel supply chain experiences a consistent trend of increase in production volumes and financial turnover since its foundation in 2005. This industry is placed at the intersection of three highly relevant national subjects: rural development, environmental sustainability and energy sustainability. Rigid framework was established throughout the supply chain due to its importance for the country. This framework has the potential to impact the performance of biodiesel production companies when neglected by them. Two types of regulation are especially important on this purpose: the auctions for biodiesel commercialization and the Social Fuel Stamp. The former is relevant for the actions of the organizations downstream of the supply chain, i.e., for the relations between the biodiesel producer companies and their clients. The latter is key for the actions of the organizations upstream the supply chain, i.e., for the relations between the biodiesel producer companies and their raw material suppliers. The most traditional concepts of business strategy are not able to provide the required theoretical tools to explain the obtainment of competitive advantage and, therefore, superior performance, since the relation between the company and the actors at the layer beyond the competitive environment. The concepts of nonmarket and nonmarket strategy present the theoretical tool to this kind of discussion. These concepts are especially valid for markets with monopolistic features or that are highly regulated. In this regard, it was established the following research question: How does nonmarket environment impact strategy and performance of the biodiesel producer firm? At the heart of this question lie two phenomena: the impact on the performance of the biodiesel producer company caused by the biodiesel auctions; and the impact on performance of the biodiesel producer company caused by the Social Fuel Stamp. From a methodological standpoint, it was adopted a phenomenological perspective for the conduction of this study, i.e., it was prioritized the understanding of the standpoints of the agents involved with the research question aiming to describe the observed phenomena and to discuss their causes. Three research strategies were adopted to drive the tasks of collecting and analyzing data: bibliographic research; bibliometric research; and grounded theory. The first two strategies aimed to delimit the state of the art about the concepts of nonmarket strategy; nonmarket environment; and studies on management in the context of the biodiesel supply chain. They were managed from the assessment of secondary data. The third strategy aimed to deeply explore the view of the agents with experience in the biodiesel industry with an eye on the relations between nonmarket environment and performance of the company. The discussions originated from data assessment were divided into two blocks: exploratory approach and theoretical approach. The former, with a descriptive purpose, exposed details on the functioning of the biodiesel auctions and of the Social Fuel Stamp, adding the first impressions on how these two issues of the nonmarket environment impact the performance of the biodiesel producer company. The latter, with a theoretical purpose, exposed details on the analytical and refining processes of the qualitative data that came from the field. It was discussed since the simplest assessments related to the frequency of words until the most sophisticated analysis of open, axial and selective coding. As core result, it is being proposed the following grounded theory: Market and nonmarket strategies are indivisible and key in the pursuit of superior performance in the Brazilian biodiesel market.